Fecal Leukocytes in Children Infected with Diarrheagenic Escherichia coli - Mercado, Erik H. (2014)
The purpose of this study was to determine the presence and quantity of fecal leukocytes in children infected with diarrheagenic Escherichia coli and to compare these levels between diarrhea and control cases. We analyzed 1,474 stool samples from 935 diarrhea episodes and 539 from healthy controls of a cohort study of children younger than 2 years of age in Lima, Peru. Stools were analyzed for common enteric pathogens, and diarrheagenic E. coli isolates were studied by a multiplex real-time PCR. Stool smears were stained with methylene blue and read by a blinded observer to determine the number of polymorphonuclear leukocytes per high-power field (L/hpf). Fecal leukocytes at >10 L/hpf were present in 11.8% (110/935) of all diarrheal episodes versus 1.1% (6/539) in controls (P < 0.001). Among stool samples with diarrheagenic E. coli as the only pathogen isolated (excluding coinfection), fecal leukocytes at >10 L/hpf were present in 8.5% (18/212) of diarrhea versus 1.3% (2/157) of control samples (P < 0.01). Ninety-five percent of 99 diarrheagenic E. coli diarrhea samples were positive for fecal lactoferrin. Adjusting for the presence of blood in stools, age, sex, undernutrition, and breastfeeding, enterotoxigenic E. coli (ETEC) isolation as a single pathogen, excluding coinfections, was highly associated with the presence of fecal leukocytes (>10 L/hpf) with an odds ratio (OR) of 4.1 (95% confidence interval [CI], 1.08 to 15.51; P < 0.05). Although diarrheagenic E. coli was isolated with similar frequencies in diarrhea and control samples, clearly it was associated with a more inflammatory response during symptomatic infection; however, in general, these pathogens elicited a mild inflammatory response.